Literatura e cultura: narrar a identidade religiosa em Viva o povo brasileiro de João Ubaldo Ribeiro - Silva, Rosângela Santos (2015)
This thesis sought to understand and analyze the narratives and representations regarding the ritualistic cult egwugwu nanny in Itaparica / BA Island from the literary Long live the Brazilian people (1984) of itaparicano João Ubaldo Ribeiro. Assuming that the theme of religiosity, this work is related to identity projects based on memory and oral aimed to reflect on the forms of African descent resistance at keeping alive the religious basis of their ancestors and how the feeling of belonging a particular religion becomes a key factor in the construction of cultural identity. The study is based on the reflection of dialogical relations between memory and orality, ritual egwugwu and performance practices carried out in Afro-Brazilian religions. Categories such as ancestry, oral, performance and ritual were triggered as reading operators, in line with the theoretical, critical and historical postulates of Literature scholars of African and Afro-Brazilian cultures. In the particular case of this work, one of the many outstanding contributions is by proposing a model of understanding and analysis of the dynamics of public performances of Candomblé. Thus, the research allowed to present a new look about the religions of African origin and their practices showing how João Ubaldo Ribeiro to transcribe these facts, it highlights something essential that is respect and appreciation for these religions who still suffer prejudice and discrimination.